A fibre optic microsensor for measurement of temperature dynamics in gas turbine systems - Kilpatrick, J; MacPherson, W; Barton, J; Jones, J; Buttsworth, DR; Jones, T; Chana, K; Anderson, J (2003)
The use of computational fluid dynamics (CFD) to model the temperature and pressure distributions which drive complex thermodynamic processes in gas turbine systems contributes to more cost efficient turbine design and development. However, experimental measurements are still required for validation of full-field CFD models, particularly in regions of highly unsteady flow where model stability is most severely tested. THis work concerns the development of fiber optic temperature and pressure microsensors for measurements combining high spatial resolution and high bandwidth in unsteady gas flows. The objective of the work presented in this paper was to measure gas total temperature in a large- scale turbomachinery test-rig at DERA Pyestock, known as the Isentropic Light Piston Facility. We have accordingly designed a dual sensor system, in which one of the elements is heated, so that gas total temperature can be measured independently of the convective heat transfer coefficient. While such dual element probes based on thin-film resistance gauges have been developed previously for aerodynamic studies, this is the first report of their development using optical sensors. ©2003 Copyright SPIE - The International Society for Optical Engineering.